Effect of prey availability on the abundance of White-breasted Wood-Wrens, insectivorous birds of tropical lowland forests - Sanchez, Natalie V. (2014)
Some understory insectivorous birds manage to persist in tropical forest fragments despite significant habitat loss and forest fragmentation. Their persistence has been related to arthropod biomass. In addition, forest structure has been used as a proxy to estimate prey availability for understory birds and for calculating prey abundance. We used arthropod biomass and forest structural variables (leaf area index [LAI] and aerial leaf litter biomass) to explain the abundance of White-breasted Wood-Wrens (Henicorhina leucosticta), tropical understory insectivorous birds, in six forests in the Caribbean lowlands of Costa Rica. To estimate bird abundance, we performed point counts (100-m radius) in two old-growth forests, two second-growth forests, and two selectively logged forests. Arthropod abundance was the best predictor of wood-wren abundance (wi = 0.75). Wood-wren abundance increased as the number of arthropods increased, and the estimated range of bird abundance obtained from the model varied from 0.51 (0.28 – 0.93 [95%CI]) to 3.70 (1.68 – 5.20 [95%CI]) within sites. LAI was positively correlated to prey abundance (P = 0.01), and explained part of the variation in wood-wren abundance. In forests with high LAI, arthropods have more aerial leaf litter as potential habitat so more potential prey are available for wood-wrens. Forests with a greater abundance of aerial leaf litter arthropods were more likely to sustain higher densities of wood-wrens in a fragmented tropical landscape.